Environmental perception, socio-economic profile and land settlement and use of Pedro de Toledo nucleus population (Parque Estadual da Serra do Mar/SP) - Fonseca de Sousa, Iara; Campos Ferreira, Léo Eduardo; Magini, Christiano; Moledo de Sousa Abessa, Denis (O Mundo da Saúde, 2006)
Pedro de Toledo Nucleus is part of Serra do Mar State Park, a category of environmental protection area that does not allow the presence of inhabitants nor the direct use of its natural resources. However, the nucleus presents human settlements, as small villages spread along its territory. The present project consisted in producing a socio-economic profile of these inhabitants. Land use and settlement were investigated, as well as the potential environmental impacts due to such land uses. To reach that, field visits were done, and semi-structured questionnaires were applied to local inhabitants. The community was considered very homogeneous, formed mainly by non-native agriculturists, and therefore can not be considered traditional. Moreover, although claiming they know legal restrictions and not to have conflicts with them, people there use land predominantly for agriculture, and also to aquaculture and recreation. From the information gathered, the need of using low-impact agricultural methods were evidenced, as well as the introduction of economic alternatives which do not imply direct use of the resources, in order to assure environmental preservation and improve quality of life of the inhabitants, until their legal situation is solved.